Registered nurses' perceptions of factors influencing nursing care quality: A structural equation modeling study - Virya Koy (2020)
© 2019 John Wiley & Sons Australia, Ltd Cambodia, like many other countries, is working to raise nursing care standards, including improving nurse work environments and nurse education. This descriptive, cross-sectional study examined the factors influencing nursing care quality among 375 registered nurses from 12 government hospitals in Cambodia. The conceptual framework was modified from the Nurse Work Environment, Nurse Staffing, and Outcome Model, and five questionnaires were used. The hypothesized model fitted the empirical data and explained 12% of the variance in nursing care quality. Structural equation modeling revealed that nurse work satisfaction negatively affected nursing care quality, while the nurse practice environment and burnout had no effect. Nurse staffing had a positive direct effect on nurse work satisfaction, while nurse work satisfaction did not directly affect burnout. The results indicate that the highest impacting factors influencing nursing care quality were nurse work satisfaction and the indirect effect of nurse staffing on nursing care quality. Therefore, leaders and policymakers in government, health systems, and nursing across the country need to consider these results to enhance nursing care quality.